The paradox of the Green Revolution in the Cerrado: The paradox of the Green Revolution in the Cerrado (Élisée - Revista de Geografia da UEG, 2020)
The purpose of this paper is to analyze the process of modernization of agriculture triggered by the Green Revolution in the Brazilian Savanna (“Cerrado”) and the social, economic and environmental transformations undergone by this space, produced and appropriated by the capital, as well as the effects of modernization on business and family agriculture. Our discussions highlight: the Green Revolution as the starting point for the modernization of agriculture in the Cerrado; the Cerrado as the territory of the technological package; some thoughts on the 1980s’ modernizing project for the Cerrado; the paradox of the modernization of agriculture, with agribusiness focused on productivity and family farming aiming for sustainability; and, finally, the visibility gained by family farming since the 1990s, in view of the debate about its importance as supplier of food for the internal market.
Keywords: Cerrado. Green Revolution. Modernization of agriculture.